Financial literacy among undergraduates: a study in Universiti Sains Malaysia - Wei Quan, Lee Chock; Yee, Whah Chin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Youth exposure to financial literacy information has become common in today's digital age, providing students with early financial management skills for a lifetime of well-being. However, easy access to technology and information doesn't always translate into financial literacy skills for today's students. This study aims to comprehensively understand financial literacy among undergraduates at Universiti Sains Malaysia, describing gender and ethnic group differences. It applied the theory of embeddedness to explain financial literacy variations across family backgrounds, friend networks, gender, and ethnicity. A single-stage non-probability sampling method was used. Employing purposive and quota sampling, ten informants from diverse backgrounds were interviewed. Grounded theory with open coding, axial coding, and selective coding was employed for data analysis. The findings show that undergraduate financial literacy is primarily shaped by family and social networks, where young individuals continuously develop and enhance their financial knowledge. The findings implied that educators and policymakers can customize strategies for young individuals, aligning financial literacy promotion with real-life experiences of young people which can contribute to long-term solutions for reducing youth bankruptcy.